PENGARUH DAYA TARIK IKLAN, EFEK KOMUNITAS, DAN BRAND ACTIVATION TERHADAP BRAND AWARENESS SIMCARD GSM PRA BAYAR IM3 (Studi Kasus Pada Mahasiswa Program Sarjana FISIP Undip Semarang) - Sukabhakti, Balantazara Bisma Yohannes; Widiartanto, Widiartanto; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2015)
The number of competitors and the competition is so tight, making the company wants consumers to remember and awaken their brand presence. The attractiveness of advertising, community effects, and brand activation are all factors that can affect brand awareness. This type of research is explanatory research. The sampling technique including nonprobability sampling is purposive sampling. The sample in this study amounted to 100 respondents who are students of S1 FISIP Diponegoro University of Semarang. In the analysis used qualitative analysis and quantitative test with SPSS 16.0. Based on analysis, community effects, and brand activation has an influence to brand awareness. Brand activation variables have the most influence is 41.4%. Meanwhile, the attractiveness of advertising and community effect has the effect of 37.4% and 14.7% to brand awareness. Simultaneously, the attractiveness of advertising, community effects, and brand activation effect on brand awareness with F count> F table (44.742> 2,70). In conclusion, the attractiveness of advertising, community effects, and brand activation effect on brand awareness. Based on these results, IM3 should focus on marketing activities such as advertising and brand activation as well as improving the effects of the community on an ongoing basis in order to brand awareness IM3 be top of mind.